New-type gel dry-water extinguishants and its effectiveness. (10th November 2017) - Han, Zhiyue; Zhang, Yupeng; Du, Zhiming; Xu, Fangrong; Li, Shulin; Zhang, Jingchang
Abstract: This work sets focus on producing hydrophobic silica and fire-extinguishing-composition solution into dry water extinguishant powder by high-speed shearing. The solid-to-liquid ratio, different stirring periods and rotational speed were taken into account to analyze their influence on the covering effect. The dry water extinguishants containing ammonium dihydrogen phosphate (ADP) and phosphoric acid are respectively produced added with gel. The jet apparatus is improved for the experiment. According to the results, the phosphoric acid gel dry water extinguishant works best to put out Type-A fire. The ADP dry water extinguishant excels in putting out Type-B fire, equivalent to superfine ABC dry powder extinguishant in terms of effectiveness but with a low cost. For this reason, dry water extinguishant has a broad prospect of application. Highlights: A new-type gel dry water extinguishant is prepared fistly. The optimal preparation technology of dry water extinguishant has been obtained. Dry water extinguishants work well to quench Type-A and B fire. The fire extinguishing mechanism of dry water extinguishant has been discussed firstly.